2021
DOI: 10.1186/s12984-021-00813-7
|View full text |Cite
|
Sign up to set email alerts
|

Wearable vibrotactile stimulation for upper extremity rehabilitation in chronic stroke: clinical feasibility trial using the VTS Glove

Abstract: Objective Evaluate the feasibility and potential impacts on hand function using a wearable stimulation device (the VTS Glove) which provides mechanical, vibratory input to the affected limb of chronic stroke survivors. Methods A double-blind, randomized, controlled feasibility study including sixteen chronic stroke survivors (mean age: 54; 1-13 years post-stroke) with diminished movement and tactile perception in their affected hand. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…This type of directed sensory rehabilitation is currently being explored, such as focal repetitive muscle vibration, which is a non-invasive post-stroke therapy to reduce muscle tone [ 42 , 43 ]. Another example is wearable focal stimulation devices, such as a vibrotactile glove (VTG), which provides vibratory input to the paretic limb of chronic stroke survivors and has been shown to promote neural plasticity and reduces spasticity [ 44 , 45 ]. Other studies have used robot-assisted somatosensory training and vibrotactile biofeedback devices [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This type of directed sensory rehabilitation is currently being explored, such as focal repetitive muscle vibration, which is a non-invasive post-stroke therapy to reduce muscle tone [ 42 , 43 ]. Another example is wearable focal stimulation devices, such as a vibrotactile glove (VTG), which provides vibratory input to the paretic limb of chronic stroke survivors and has been shown to promote neural plasticity and reduces spasticity [ 44 , 45 ]. Other studies have used robot-assisted somatosensory training and vibrotactile biofeedback devices [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This type of directed sensory rehabilitation is currently being explored, an example of this is wearable focal stimulation devices, such as a vibrotactile glove (VTG). VTGs provide vibratory input to the paretic limb of chronic stroke survivors and have been shown to promote neural plasticity and reduce spasticity [45,46]. Other studies have used robot-assisted somatosensory training and vibrotactile biofeedback devices [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…A recent report indicated that the vibrotactile component of the haptic feedback that occurs when playing a musical instrument leads to increased quality of hand perceptions [41]. Due to central mechanisms, vibrotactile stimulation on the ngertips results in not only activating cutaneous mechanoreceptors, but it also enhances the mechanical coupling between the contacted skin, tendons, and bones, which signi cantly improves the of touch-pressure threshold, as tested by Semmes-Weinstein mono lament [42] and the capacity of active force perception as measured when participants manipulate objects [43].…”
Section: Discussionmentioning
confidence: 99%